ANALISIS PERBANDINGAN TOOLKIT RECUVA DATA RECOVERY DAN STELLAR PHOENIX WINDOWS DATA RECOVERY UNTUK DIGITAL FORENSIK - Handrizal Handrizal (semanTIK, 2018)
This paper presents an analysis with two digital forensic toolkits for deleted data scenarios. The used toolkit is Recuva Data Recovery and Stellar Phoenix Windows Data Recovery. They can recover data that is being and analyzed in a USB flash drive. The results of the comparison that the two toolkits can work well regarding finding data that has been discarded or in recovering the deleted data.Keywords—Data, Recovery, Forensic, Recuva, Stellar DOI: 10.5281/zenodo.1438737